Interactions of Arene-Ru(II)-Chloroquine Complexes of Known Antimalarial and Antitumor Activity with Human Serum Albumin (HSA) and Transferrin - Martínez, Alberto (2011)
The interactions of π-arene-Ru(II)-chloroquine complexes with human serum albumin (HSA), apotransferrin and holotransferrin have been studied by circular dichroism (CD) and UV-Visible spectroscopies, together with isothermal titration calorimetry (ITC). The data for [Ru(η(6)-p-cymene)(CQ)(H(2)O)Cl]PF(6) (1), [Ru(η(6)-benzene)(CQ)(H(2)O)Cl]PF(6) (2), [Ru(η(6)-p-cymene)(CQ)(H(2)O)(2)][PF(6)](2) (3), [Ru(η(6)-p-cymene)(CQ)(en)][PF(6)](2) (4), [Ru(η(6)-p-cymene)(η(6)-CQDP)][BF(4)](2) (5) (CQ: chloroquine; DP: diphosphate; en: ethylenediamine), in comparison with CQDP and [Ru(η(6)-p-cymene)(en)Cl][PF(6)] (6) as controls demonstrate that 1, 2, 3, and 5, which contain exchangeable ligands, bind to HSA and to apotransferrin in a covalent manner. The interaction did not affect the α-helical content in apotransferrin but resulted in a loss of this type of structure in HSA. The binding was reversed in both cases by a decrease in pH and in the case of the Ru-HSA adducts, also by addition of chelating agents. A weaker interaction between complexes 4 and 6 and HSA was measured by ITC but was not detectable spectroscopically. No interactions were observed for complexes 4 and 6 with apotransferrin or for CQDP with either protein. The combined results suggest that the arene-Ru(II)-chloroquine complexes, known to be active against resistant malaria and several lines of cancer cells, also display a good transport behavior that makes them good candidates for drug development.